The Impact of Hedge Fund Activism on the Target Firm's Existing Bondholders - Klein, April; Zur, Emanuel (Review of Financial Studies, 2011)
[In contrast to previous studies documenting positive abnormal returns to target shareholders, we find that hedge fund activism significantly reduces bondholders' wealth. The average excess bond return is —3.9% around the initial 13D filing, and is an additional —4.5% over the remaining year. Excess bond returns are related inversely to subsequent changes in cash and assets (loss of collateral effects) and directly to changes in total debt. Confrontational campaigns and the acquisition of at least one seat on the target's board elicit more negative bond returns. We also find an expropriation of wealth from the bondholder to the shareholder.]